Optical method to preserve residual hearing in patients receiving a cochlear implant - Cury, Joaquin; Rivera, Arnaldo; Schneider, Rebecca; Tan, Ray; Tan, Xiaodong; Richter, Claus-Peter (Frontiers in Audiology and Otology, 2024)
Introduction Worldwide, thousands of patients with severe to profound hearing loss restore their hearing with cochlear implant (CI) devices. Newer developments in electrode design and manufacturing and a better understanding of cochlear mechanics allow for conserving critical structures, often translating into serviceable residual hearing and improving device performance. Monitoring insertion speed and intraluminal pressure helps mitigate some of these challenges. However, the information becomes available after irreparable damage has occurred. Methods We developed and tested a high-resolution optical system to navigate the intricate anatomy of the cochlea during electrode insertion. The miniaturized optical system was integrated in conventional cochlear implants electrode arrays and custom-made cochlear probes. Electrode insertion were conducted in eight cadaveric human temporal bones and video recordings were acquired. Micro-computed tomography (μCT) scans were performed to evaluate the position of the modified electrode arrays. Results Full insertions of the modified CI electrode were successfully conducted and verified by μCT scans. Video recordings of the cochlear structures visible in scala tympani were acquired, and no scala migration was detected. Discussion Surgeons can now follow the CI electrode's path during its insertion and reduce cochlear damage through early interventions and steering of the CI electrode. Our device will be compatible with robotic platforms that are already available to insert these electrodes.